Terapi Nonfarmakologi Berbahan Herbal Untuk Menurunkan Nyeri Rematik - Kartila, Dewi; Ratnasari, Duwi; Yani, Anggria; Anjani, Evi; Nanda, Shafira Dian; Putri, Yesi; Rohani, Tuti; Azissah, Danur (LPPM Universitas Dehasen Bengkulu, 2025)
Rheumatoid Arthritis is an autoimmune disease that causes chronic inflammation of the joints, characterized by pain and reduced mobility, which significantly impacts the quality of life of its sufferers. This study aims to analyze the effectiveness of an herbal remedy containing ginger, galangal, and lemongrass in reducing pain intensity among Rheumatoid Arthritis patients. The research employed a quantitative approach with a pre-experimental design. It was conducted in RT 05, Kelurahan Ponorogo, Kecamatan Lubuklinggau Utara II, involving 20 purposively selected respondents. The herbal remedy was administered twice daily for seven days, and pain intensity was measured using the Visual Analog Scale (VAS) before and after the intervention.The results showed a significant decrease in the average pain intensity from 6.5 to 3.0 after the intervention (p < 0.05). The gingerol content in ginger, flavonoids in galangal, and anti-inflammatory compounds in lemongrass were found to play a role in reducing inflammation and joint pain. This herbal remedy is effective, safe, and easily applicable as an alternative therapy for Rheumatoid Arthritis patients, particularly in communities with limited access to pharmacological treatments. The study concludes that the herbal remedy of ginger, galangal, and lemongrass is a potential option in Rheumatoid Arthritis management. Further research is recommended to strengthen these findings.